2021
DOI: 10.3390/vaccines9121395
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination in Patients with Pulmonary Arterial Hypertension and Chronic Thromboembolic Pulmonary Hypertension: Safety Profile and Reasons for Opting against Vaccination

Abstract: The incidence of COVID-19 infection in patients with pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) is similar to that in the general population, but the mortality rate is much higher. COVID-19 vaccination is strongly recommended for PAH/CTEPH patients. The aim of our cross-sectional study was to identify reasons why PAH/CTEPH patients refused vaccination against COVID-19. Moreover, we assessed the safety profile of approved COVID-19 vaccines in PAH/CTEPH patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
(47 reference statements)
0
15
0
1
Order By: Relevance
“…It has proven to be safe in PAH and CTEPH patients. 26 During the last pandemic wave due to the Omicron variant, we reported the highest incidence of all the pandemic period with 17 cases over one single month. Two of these patients were unvaccinated and only one of them required hospital admission.…”
Section: Discussionmentioning
confidence: 80%
“…It has proven to be safe in PAH and CTEPH patients. 26 During the last pandemic wave due to the Omicron variant, we reported the highest incidence of all the pandemic period with 17 cases over one single month. Two of these patients were unvaccinated and only one of them required hospital admission.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies had demonstrated a significant positive correlation between COVID-19 vaccination willingness and vaccination uptake behavior in patients with T2DM [ 19 ]. Groups of chronically ill patients, including those with diabetes, have lower COVID-19 vaccination rates, such as 8.3% in the U.S. and 18% in France [ 20 , 21 ]. However, the general population of patients with chronic diseases varies greatly by disease type, resulting in a limited representation of the behaviors of the massive number of diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, there was no vaccination prioritization for PAH/CTEPH patients, even if they were seriously ill, except for patients waiting for a lung transplant. At the end of our study, 85% of PAH/CTEPH patients had been vaccinated, but in mid-June 2021 the figure was only 43% [22]. Some of the previously unvaccinated patients changed their minds after they caught COVID-19, while some changed their minds after attending informative campaigns organized at study centers.…”
Section: Discussionmentioning
confidence: 78%